Meet cute [videorecording (DVD)] - Pnueli, Noga; Davidson, Pete, 1993-; Cuoco, Kaley; Craig, Deborah S.; Corrigan, Kevin, 1969- (Universal, 2023)
When Sheila and Gary meet, it's love at first sight. Turns out, their magical date wasn't fate at all: Sheila's got a time-traveling tanning bed hidden inside a nail salon, and they've been falling in love over and over again. But when the perfect night is never quite enough, Sheila travels to Gary's past to change him into the perfect man.